Impact of knowledge-based organizational support on organizational performance through project management (2022)
ABSTRACT: Purpose –The purpose of this study is to empirically investigate how knowledge-based organizationalsupport (KOS) influences organizational performance through project management.Design/methodology/approach –Data were obtained from a survey and from archival sources with atime lag for the dependent variable; structural equation modeling was used to analyze the data. Thesample was made up of 106 organizations in Colombia, considering two key respondents from eachorganization: general manager and project manager.Findings –Results show that KOS is an antecedent of project management and project performance.Furthermore, project management and project performance play a mediating role between KOS andorganizational performance.Research limitations/implications –Research limitations are the following: use of cross-sectional datawith a time lag, one single unit of analysis, organizational performance analyzed only from a financialperspective. Despite these limitations, the paper puts forward relevant implications that bridge knowledgemanagement and project management literature by clarifying the conditions under which knowledgeorganizational support generates a significant impact on organizational performance. Intellectual capitaland knowledge management dynamic capabilities play a relevant role in this connection.Practical implications –The findings have important practical implications: decision-makers are toallocate effectively hard and soft resources to configure a knowledge-based infrastructure, through thedevelopment of intellectual capital and knowledge management dynamic capabilities.Social implications –The findings are generalizable to projects management in the context of non-government organizations or other social-oriented initiatives.Originality/value –This study assumes and operationalizes organizational support from a knowledge-based perspective, represented by intellectual capital and knowledge management dynamiccapabilities, providing empirical evidence of the way KOS influences organizational performancethrough project management and project performance.